2005
DOI: 10.1080/13638490410001727428
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of physical activity for children with acute lymphoblastic leukaemia

Abstract: Acute lymphoblastic leukaemia (ALL) is the most common form of paediatric leukaemia. The survival rate in children with ALL has improved significantly over the past several years, which makes quality of life an important focus for researchers. Some of the side effects of treatment (i.e. osteoporosis and obesity) are not realized until years after conclusion of therapy. Few studies have addressed the impact of physical activity (PA) on the side effects that occur during treatment of children with ALL. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 57 publications
0
37
1
1
Order By: Relevance
“…Activity patterns and percentage contributions of activity among leukemia patients (n = 38). which may alter the child's perception of their capability for physical activity, resulting in a fear of overexertion and low self-efficacy [7,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Activity patterns and percentage contributions of activity among leukemia patients (n = 38). which may alter the child's perception of their capability for physical activity, resulting in a fear of overexertion and low self-efficacy [7,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…[19,20] Physical activity is also important to children with asthma. In recent years, research has shown that taking part in sports can help reduce hospital admissions, reduce absenteeism …”
Section: Discussionmentioning
confidence: 99%
“…Regarding healthy children and those with conventional therapy for ALL, an increasing amount of data have been published on the beneficial effects of physical activity on weight control, type II diabetes, blood pressure, osteoporosis, psychological well being and fatigue, with many of them being a special risk for transplanted children. 25 Adult long-term survivors of childhood ALL were more likely to be physically inactive than was the general population. 26 In our study, among the patients tested for 4 or more years after SCT, the sports club members had better results in all tests when compared with others.…”
Section: Discussionmentioning
confidence: 99%